New Strategy for Inducing Surface Anisotropy in Polyimide Films for Nematics Orientation in Display Applications - Elena-Luiza Epure (MDPI AG, 2021)
The operability of liquid crystal displays is strongly impacted by the orientation aspects of nematics, which in turn are affected by the alignment layer surface features. In this work, two polyimide (PI) structures are obtained based on a cycloaliphatic dianhydride and aromatic or aliphatic diamines with distinct flexibility. The attained PI films have high transmittance (T) for visible radiations, i.e., at 550 nm T > 80%. Here, a novel strategy for creating surface anisotropy in the samples that combines rubbing with a cloth and stretching via pressing is reported. Birefringence and atomic force microscopy (AFM) scans reveal that the generated orientation of the chains is affected by the chemical structure of the polymer and order of the steps involved in the surface treatment. Molecular modeling computations and wettability tests show that the PI structure and produced surface topography are competitive factors, which are impacting the intensity of the interactions with the nematic liquid crystals. The achieved results are of great relevance for designing of reliable display devices with improved uniform orientation of liquid crystals.